2008
DOI: 10.1667/rr1199.1
|View full text |Cite
|
Sign up to set email alerts
|

Low Doses of Very Low-Dose-Rate Low-LET Radiation Suppress Radiation-Induced Neoplastic TransformationIn Vitroand Induce an Adaptive Response

Abstract: The purpose of this study was to determine whether adaptation against neoplastic transformation could be induced by exposure to very low-dose-rate low-LET radiation. HeLa x skin fibroblast human hybrid cells were irradiated with approximately 30 kVp photons from an array of (125)I seeds. The initial dose rate was 4 mGy/day. Cell samples were taken at four intervals at various times over a period of 88 days and assayed for neoplastic transformation and the presence of reactive oxygen species (ROS). The dose rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 47 publications
3
33
0
Order By: Relevance
“…are dependent on dose rate. This in vivo evidence for the dose rate dependency of protective adaptive response thresholds is therefore entirely consistent with the cell based evidence (Shadley and Wiencke 1989;Broome et al 2002;Elmore et al 2008).…”
Section: Cancersupporting
confidence: 86%
See 1 more Smart Citation
“…are dependent on dose rate. This in vivo evidence for the dose rate dependency of protective adaptive response thresholds is therefore entirely consistent with the cell based evidence (Shadley and Wiencke 1989;Broome et al 2002;Elmore et al 2008).…”
Section: Cancersupporting
confidence: 86%
“…Using a human hybrid cell line Elmore et al (2008) have reported that 100 mGy at dose rates of 1-4 mGy/day was able to induce an adaptive response that protected against spontaneous neoplastic transformation. However, at dose rates below about 1 mGy/day that suppression was lost, again suggesting that the lower dose threshold for adaption depends on the presence of a minimum number of lesions per unit time.…”
Section: Lower Dose Thresholdsmentioning
confidence: 99%
“…It can appear as damaging or protective effects in dependence on dose and dose rate. A very low dose of photon radiation (~ 30 keV) emitted by iodine-125 radioisotope (4mGy dose/day to 1,4 mGy/day) during a three month exposure of hybrid HeLa cells with human fibroblasts caused resistance of these cells to neoplastic transformation when they were challenged by subsequent irradiation with 3 Gy of 137 Cs gamma rays (Elmore et al, 2008). Lowering of dose rate below 1mGy/day abolished the adaptive answer, suggesting that low dose-rate above a certain threshold is responsible for this type of radio-adaptation.…”
Section: Radionuclide Induced Bystander Effectmentioning
confidence: 99%
“…Interestingly, these data also indicated that very low doses of radiation reduced to levels of neoplastic transformation frequency below that of the unirradiated spontaneous controls. Several studies have explored these very low-dose adaptive responses in CGL1 cells (77,(82)(83)(84)(85)(86)(87). In one of the initial studies, CGL1 cells were irradiated with 1 cGy of gamma radiation and incubated for 24 h (88).…”
Section: Adaptive Response and Bystander Effect Studies With Cgl1mentioning
confidence: 99%
“…If we observe differences in the CGL1 cells grown at ultra-low-dose radiation levels down in SNOLAB versus CGL1 cells grown natural background radiation (NBR) levels at the surface lab, we will evaluate gene expression differences by cDNA microarray and quantitative RT-qPCR assays to observe regulatory changes that may occur as culture time in the sub-NBR increases analyses and determine the genetic and epigenetic mechanisms driving these changes and will provide important mechanistic information in the evaluation of how ultra-low doses of radiation alter CGL1 cells. The Western Blue based CGL1 cell neoplastic transformation assay is highly sensitive and has been used to detect very small changes spontaneous transformation frequency when the cells are irradiated with a few mGy of ionizing radiation (82,83,85,87,88,103). Therefore, we propose that in the ultra-low radiation environment that SNOLAB provides, the CGL1 based transformation assay is ideal to detect small changes in spontaneous background neoplastic transformation frequency.…”
Section: Future Directions: Cgl1 Ultra-low-dose Studiesmentioning
confidence: 99%